Using an extended protection motivation theory to explain vaccine hesitancy: a cross-sectional study among Chinese adults - Minqi Liu; Tingting Cui; Qiang Wang; Ying Han; Yue Han; Liuqing Yang; Naiyang Shi; Youqin Yi; Hui Jin (Taylor & Francis Group, 2022)
Background Vaccine hesitancy was listed as one of the top 10 issues threatening global health in 2019. The objectives of this study were to (a) use an extended protection motivation theory (PMT) with an added trust component to identify predictors of vaccine hesitancy and (b) explore the predictive ability of vaccine hesitancy on vaccination behavior. Methods We conducted an online questionnaire from February 9 to April 9, 2021, in China. The target population was Chinese residents aged 18 and over. A total of 14,236 responses were received. Structural equation modeling was used to test the extended PMT model hypotheses. Results A total of 10,379 participants were finally included in this study, of whom 52.0% showed hesitancy toward vaccination. 2854 (27.5%) participants reported that they got flu shots in the past year, and 2561 (24.7%) participants were vaccinated against COVID-19. 2857 (27.5%) participants engaged in healthcare occupation. The model explained 85.7% variance of vaccine hesitancy. Self-efficacy was the strongest predictor, negatively associated with vaccine hesitancy (β = −0.584; p < .001). Response efficacy had a negative effect on vaccine hesitancy (β = −0.372; p < .001), while threat appraisal showed a positive effect (β = 0.104; p < .001). Compared with non-health workers, health workers showed more vaccine hesitancy, and response efficacy was the strongest predictor (β = −0.560; p < .001). Vaccine hesitancy had a negative effect on vaccination behavior (β = −0.483; p < .001), and the model explained 23.4% variance of vaccination behavior. Conclusions This study demonstrates that the extended PMT model is efficient in explaining vaccine hesitancy. However, the predictive ability of vaccine hesitancy on vaccination behavior is limited.